Impact of Flower Position and Pollinator Diversity on Yield Parameters of Pomegranate (Punica granatum L.) - Vijayakaumar, K. T.; Nithin Kumar, H. L.; Rakshita, T. N.; Nayimabanu, T. (Sociobiology, 2024)
The present study investigated the flower position characteristics of Pomegranate (variety: Bhagwa) pollinator diversity and their effect on fruit yield. The study covered floral biology, fruit attributes related to size, flower vigor, stigma receptivity, and aril development. The presence of both staminate (male) and hermaphrodite (bisexual) flowers in pomegranate allows it to be self- and cross-pollinated. The pomegranate inflorescence is a cyme. Flowers can appear solitary on spurs and in pairs or clusters terminally. The study revealed that the weight of pomegranate fruit resulting from the solitary flower was higher (351 g) with a greater number of arils (743 per fruit) than the fruit from the terminal flower (306.67 g and 620 arils) and lateral flower (221 g and 352 arils). Studies on modes of pollination provide evidence that qualitative and quantitative traits of fruits were improved by open and Apis cerana pollination. A total of 19 species of flower visitors were recorded. Apis dorsata was the primary flower visitor, followed by A. florea and A. cerana. The yield per plant under open conditions was 24.93 kg, which was on par with bee-pollinated (22.76 kg) and significantly higher than the control (15.36 kg).